Genetic variation of the blood coagulation regulator tissue factor pathway inhibitor and venous thromboembolism among middle‐aged and older adults: A population‐based cohort study - Manderstedt, Eric; Lind‐Halldén, Christina; Halldén, Christer; Elf, Johan; Svensson, Peter J.; Engström, Gunnar; Melander, Olle; Baras, Aris; Lotta, Luca A.; Zöller, Bengt; Abecasis, Goncalo; Baras, Aris; et al. (Research and practice in thrombosis and haemostasis, 2022)
Tissue factor is the main initiator of blood coagulation, and tissue factor pathway inhibitor (TFPI) is the primary inhibitor of the initiation of blood coagulation. The genetic variation of TFPI and the relation to venous thromboembolism (VTE), that is, venous thrombosis and pulmonary embolism, remains to be clarified. This exome sequencing study aimed to determine the molecular epidemiology of the TFPI gene and the relation to VTE in a large population‐based cohort of middle‐aged and older adults. The exomes of TFPI were analyzed for variants in 28,794 subjects without previous VTE (born 1923–1950, 60% women), who participated in the Malmö Diet and Cancer Study (1991–1996). Patients were followed until the first event of VTE, death, or 2018. Qualifying variants were defined as loss‐of‐function or nonbenign (PolyPhen‐2) missense variants with minor allele frequency less than 0.1%. No common variant was associated with VTE. Nine rare variants (two loss‐of‐function and seven nonbenign missense) were classified as qualifying and included in collapsing analysis. Prevalence of qualifying variants was 0.09%. Five individuals with VTE compared to 17 individuals without VTE carried one qualifying variant. Cox multivariate regression analysis adjusted for age, sex, body mass index, systolic blood pressure, smoking and alcohol consumption, rs6025, rs1799963, and ancestry showed a hazard ratio of 2.9 (95% CI, 1.2–7.1) for rare qualifying variants. Rare qualifying TFPI variants were associated with VTE, suggesting that rare variants in TFPI contribute to the development of VTE. The qualifying TFPI gene variants were very rare, suggesting a constrained gene. [Display omitted]